Titling and Beyond : Evidence from Dar es Salaam, Tanzania - Panman, Alexandra; Lozano Gracia, Nancy (World Bank, Washington, DC, 2021)
Land titling has been a policy priority for developing country cities for decades. In Sub-Saharan Africa and across the world, tenure formalization has been promoted as a tool to improve the quality and value of urban housing. The track record of these projects, however, has generally been disappointing. Why is this? This paper argues that project design has paid too little attention to contextual features of land markets in estimating the benefits of formalization to individual households. The paper draws on evidence from a case study city — Dar es Salaam, Tanzania — to show that in cities where broader property rights institutions are incomplete and informal sources of tenure security are strong, formal property rights may not be valued by households. This raises questions about the households’ willingness to pay for regularization and suggests that complementary strategies to build trust in government and consolidate public benefits of titling will be needed to ensure that projects have a beneficial impact.